Turnkey Contract - A Management Challenge under Himalayan Geological Condition - Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Himalayan geology poses special attention and tunneling challenges, which are associated to the engineering geological conditions in the rock mass. Completing tunneling project within scheduled contractual time is an issue to be carefully brainstormed and planned by a very competent project management team. This team work is especially a key demand for the projects built under turnkey contract having fixed performance guarantees, completion milestones and contract sum. This is because, delay in construction completion will bring huge contractual penalties and extra cost to the contractor and is, therefore, a management headache to the project team. Hydropower projects consisting long underground waterways system passing through varying geological ground conditions may hinder achieving targeted milestones due to uncertainty associated to the geological risks. This paper present Khimti I Hydropower Project (60 MW) that has 10 km long underground waterway system, one km long access tunnel, many construction Adits and an underground powerhouse. The project was constructed under a turnkey contract called KC2 contracts with main civil contractor responsible for both design and construction implementation of the project. The construction quality was guaranteed through several contractual performance tests listed under the KC2 contract. This article attempts to review on the way the geological ground condition has influenced in the completion milestone of the project and highlights on what are the key issues that must be carefully accessed before accepting a turnkey contract for hydropower project with long underground waterway systems. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 17-24